Nissaiyyah Learning as a Character Education Strategy for Female Students of Al-Istiqamah Islamic Ngatabaru Boarding School - Irma Anthie; Nurdin Nurdin; Ubadah Ubadah; Andi Anirah; Muhammad Wahyudi Pratama (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study examines nissaiyyah learning as a character education strategy for female students at Pondok Pesantren Al-Istiqamah Ngatabaru. Rooted in Islamic moral and etiquette teachings, the program aims to strengthen values such as honesty, modesty, and respect through structured learning activities. The urgency of this study lies in the need to maintain Islamic moral standards while addressing modern social challenges faced by young women in Islamic boarding school environments. The research employed a qualitative descriptive approach, using observations, in-depth interviews with teachers and students, and documentation analysis to capture both instructional practices and behavioral changes. The data were analyzed thematically, guided by a conceptual framework linking teaching strategies, value internalization, and character formation. Findings revealed that interactive teaching methods such as role play, storytelling, and peer discussions significantly increased student engagement and moral awareness. Adaptations of nissaiyyah content to digital etiquette and contemporary issues enhanced its relevance, while integration with Qur'an memorization reinforced discipline and patience. Teachers' consistent role modeling emerged as a critical factor in embedding values into students' daily behavior.